2011
DOI: 10.1371/journal.pone.0025683
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Eosinophil Apoptosis by the Cyclin-Dependent Kinase Inhibitor AT7519 Promotes the Resolution of Eosinophil-Dominant Allergic Inflammation

Abstract: BackgroundEosinophils not only defend the body against parasitic infection but are also involved in pathological inflammatory allergic diseases such as asthma, allergic rhinitis and contact dermatitis. Clearance of apoptotic eosinophils by macrophages is a key process responsible for driving the resolution of eosinophilic inflammation and can be defective in allergic diseases. However, enhanced resolution of eosinophilic inflammation by deliberate induction of eosinophil apoptosis using pharmacological agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
2
31
1
Order By: Relevance
“…Although one study group found that the CDKi roscovitine induced eosinophil apoptosis in vitro, they did not find any significant effect of roscovitine when administered in a model of allergic inflammation in vivo with respect to airway or tissue eosinophilia, nor was any difference in goblet cell mucus production noted (39). This is in partial contrast to a previous study by our group in which we used a different CDKi (AT7519) where administration in a model of allergic pleurisy was able to reduce eosinophil numbers at the site of inflammation secondary to enhanced eosinophil apoptosis (40), although the functional effects of this CDKi-mediated reduction in eosinophils were not investigated. Similarly, in a recent investigation, mice deficient in Siglec-F signaling demonstrated enhanced eosinophilic airway inflammation, presumed secondary to a reduction in eosinophil apoptosis (41).…”
Section: Discussioncontrasting
confidence: 87%
“…Although one study group found that the CDKi roscovitine induced eosinophil apoptosis in vitro, they did not find any significant effect of roscovitine when administered in a model of allergic inflammation in vivo with respect to airway or tissue eosinophilia, nor was any difference in goblet cell mucus production noted (39). This is in partial contrast to a previous study by our group in which we used a different CDKi (AT7519) where administration in a model of allergic pleurisy was able to reduce eosinophil numbers at the site of inflammation secondary to enhanced eosinophil apoptosis (40), although the functional effects of this CDKi-mediated reduction in eosinophils were not investigated. Similarly, in a recent investigation, mice deficient in Siglec-F signaling demonstrated enhanced eosinophilic airway inflammation, presumed secondary to a reduction in eosinophil apoptosis (41).…”
Section: Discussioncontrasting
confidence: 87%
“…Glucocorticoids, such as dexamethasone, have been extensively used to treat allergic diseases such as asthma. Glucocorticoid induction of eosinophil apoptosis has been proposed as a key mechanism to reduce tissue and circulating eosinophil numbers [59][60][61][62][63]. Our results clearly demonstrate that gedunininduced eosinophil arrest is a result of the impairment of the T cell-dependent eosinophilotactic mediators IL-5, CCL11 and CCL5, even though gedunin also presents direct effects on isolated eosinophils (impairing chemotaxis), as we have previously demonstrated [30].…”
Section: Discussionsupporting
confidence: 81%
“…CDK inhibitor drugs drive neutrophil and eosinophil apoptosis in vitro and enhance resolution of inflammation in vivo 12133637. Previous work from our group found that the flavone compound wogonin, which inhibits CDK9 in cancer cells38 can drive neutrophil apoptosis in a zebrafish tailfin wounding model21.…”
Section: Discussionmentioning
confidence: 98%